Prophyll in Monocots: The Starting Point of Lateral Shoot Phyllotaxis - Choob, Vladimir (Frontiers in Plant Science, 2022)
In monocots, the prophyll (or flower bracteole) is the first leaf of the lateral shoot. Typically, the prophyll occurs in an adaxial position toward the main axis; it bears two teeth at its apex and often two keels on the dorsal side. Some authors have hypothesized that the prophyll appeared in evolution as a result of the fusion of two phyllomes. However, in different monocot taxa, prophyll morphology results from the mechanical pressure of the surrounding organs and it cannot be regarded as two fused leaves. In Commelinaceae, if the lateral shoot develops extravaginally (i.e., penetrates the sheath) and the prophyll is not under pressure, the apical teeth and keels are missing. If the lateral shoot starts development intravaginally and under moderate pressure, the prophyll exhibits keels and a bidentate shape. In the bulbs of Amaryllidaceae, which are under strong pressure, the teeth of the prophyll become more pronounced, and the prophyll is dissected into two distinct lobes. In some monocots, the evolutionary trend leads to complete prophyll reduction. Investigations of lateral shoot phyllotaxis have found that the positions of all the subsequent phyllomes of the lateral shoot are sensitive to the prophyll position; they become rearranged if the prophyll deviates from the standard adaxial location (e.g., becoming oblique or transversal). As a generalization in Amaryllidaceae, I have proposed the axiomatic “phantom” method for modeling the prophyll position and shoot branching in cases of complete prophyll reduction. Using the phantom method, I reinvestigated the structure of sympodial units in Philodendron (Araceae). Previous interpretation of the two-keeled cataphyll as a prophyll appeared to be erroneous. In a new interpretation of the sympodial unit, the prophyll and the subsequent leaf are reduced and the cataphyll is the third leaf in the leaf series. A comparative morphological study in Araceae has revealed that prophylls of vegetative shoots rarely elongate and resemble round scales with obscure boundaries with the main axis. This observation could explain prophyll reduction in Philodendron. As such, the positional control of phyllotaxis by the prophyll may be revealed even when the prophyll is completely reduced.